A New Method for the Synthesis of Oxadiazine Insecticide Indoxacarb. (19th June 2015) - Xu, Defeng; Guan, Jing; Xu, Xing; Gong, Shunze; Xu, Hui
Abstract : 9‐Fluorenylmethoxycarbonyl was a good protecting group in the field of chemical industry. In the present paper, a new approach for the synthesis of oxadiazine insecticides indoxacarb used 9‐fluorenylmethoxycarbonyl as protected group, and triphosgene forchloroformylation . A convenient synthesis of 9‐fluorenylmethoxycarbonylhydrazine can be achieved by thenucleophilic substitution reaction of 9‐fluorenylmethyl chloroformate and hydrazine hydrate. 4a‐Methyl‐2‐(9‐fluorenylmethyl)‐7‐chloro‐indeno [1, 2e][1, 3, 4]oxadia zine‐2, 4a (3H, 5H)‐dicarboxylate can be produced via ketone ‐hydrazine crosslink reaction andcyclization . A preparation of carbamic acid‐(chlorocarbonyl)‐[(4‐trifluoromethoxy) phenyl] me ester can be obtained by thechloroformylation of triphosgene. Finally, thedeprotection of 9‐fluorenylmethoxy carbonyl and condensation with carbamic acid‐(chlorocarbonyl)‐[(4‐trifluoromethoxy) phenyl] me ester can afford indoxacarb in good yield. A new method for the synthesis of oxadiazine insecticides indoxacarb used 9‐fluorenylmethoxycarbonyl‐protected group to produce 9‐​fluorenylmethoxycarb​onylhydrazine, then through the ketone–hydrazine crosslink reaction, cyclization, deprotection, chloroformylation, and condensation in good yield. Abstract :